2013
DOI: 10.1371/journal.pone.0075029
|View full text |Cite
|
Sign up to set email alerts
|

High Genetic Diversity and Distinctiveness of Rear-Edge Climate Relicts Maintained by Ancient Tetraploidisation for Alnus glutinosa

Abstract: Populations located at the rear-edge of a species’ distribution may have disproportionate ecological and evolutionary importance for biodiversity conservation in a changing global environment. Yet genetic studies of such populations remain rare. This study investigates the evolutionary history of North-African low latitude marginal populations of Alnus glutinosa Gaertn., a European tree species that plays a significant ecological role as a keystone of riparian ecosystems. We genotyped 551 adults from 19 popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 70 publications
3
58
1
2
Order By: Relevance
“…This model has recently been challenged by a continentwide population genetic study (Havrdová et al 2015), suggesting that multiple refugia served as sources for the postglacial colonization of Europe by A. glutinosa, central Europe being an area of genetic admixture between western and eastern lineages originating from the northern part of the Iberian Peninsula and the Carpathians, respectively. Using SSR markers, Lepais et al (2013) showed a strong distinctiveness of Moroccan populations of A. glutinosa in the rear-edge distribution margins of the species. Recently, two studies using SSR markers have shown high levels of genetic diversity and very little differentiation between Irish A. glutinosa populations (Beatty et al 2015;Cubry et al 2015).…”
Section: Communicated By P Ingvarssonmentioning
confidence: 95%
“…This model has recently been challenged by a continentwide population genetic study (Havrdová et al 2015), suggesting that multiple refugia served as sources for the postglacial colonization of Europe by A. glutinosa, central Europe being an area of genetic admixture between western and eastern lineages originating from the northern part of the Iberian Peninsula and the Carpathians, respectively. Using SSR markers, Lepais et al (2013) showed a strong distinctiveness of Moroccan populations of A. glutinosa in the rear-edge distribution margins of the species. Recently, two studies using SSR markers have shown high levels of genetic diversity and very little differentiation between Irish A. glutinosa populations (Beatty et al 2015;Cubry et al 2015).…”
Section: Communicated By P Ingvarssonmentioning
confidence: 95%
“…Moreover, ancient tetraploidization probably allowed the species to maintain high genetic diversity and adaptability in the rear‐edge climate relicts of northern Africa, by increasing the effective population size, which further corroborates the adaptive potential of the species (Lepais et al . ). A previous landscape genetic study based on 163 AFLP markers already suggested a signal of adaptation to climate conditions in Europe (Cox et al .…”
Section: Introductionmentioning
confidence: 97%
“…More recently, the existence of both refugia in Belarus and western Russia has been demonstrated; they were important sources for northward post-glacial expansion of alders (Douda et al, 2014). Today, A. glutinosa populations are still marked by recent isolation in glacial refugia (King & Ferris, 1998), and several unique chloroplast haplotypes have been detected in relict populations from Morocco (Lepais et al, 2013) and Turkey (King & Ferris, 1998; Havrdová et al, 2015). Of interest, the high genetic diversity detected in Turkey concurs with the observed morphological variations of A. glutinosa in this region.…”
Section: Introductionmentioning
confidence: 99%